2018
DOI: 10.11622/smedj.2018034
|View full text |Cite
|
Sign up to set email alerts
|

Authors’ reply: Comment on: Empathy and burnout: a study on residents from a Singapore institution

Abstract: Burnout comprises three interrelated dimensions: emotional exhaustion (EE), depersonalisation (DP) and low personal accomplishment (PA). (2) The Maslach Burnout Inventory (MBI) is the most frequently used questionnaire and includes 22 items that measure all three burnout dimensions (seven-item EE subscale, eight-item PA subscale and seven-item DP subscale). Although several studies focus on the presence of high levels of EE or DP alone, other burnout studies have also included all three components in their mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Malignancy was noted in 7 women, out of whom 2(4%) had endometrial and 5(10%) had cervial cancer. Gredmark T et al, Lee WH et al Dangal G et al and by Kaur M et reported atropic endomaterium in 49.9%, 52.1%, 64.4% and 53% repectively, which the commonest cause for the postmenopausal bleeding where as in our study the reported prevalance was only 7(14%) to be atrophy [13,23,14,15] . Meyer et al postulated the reason for the post-menopausal bleed in senile endometrium to be sclerotic degeneration of endometrial vessels whereas Hourihan et al stated that the anatomical vascular variations or local abnormal haemostatic mechanisms in the uterus to be the cause.…”
Section: Resultssupporting
confidence: 50%
“…Malignancy was noted in 7 women, out of whom 2(4%) had endometrial and 5(10%) had cervial cancer. Gredmark T et al, Lee WH et al Dangal G et al and by Kaur M et reported atropic endomaterium in 49.9%, 52.1%, 64.4% and 53% repectively, which the commonest cause for the postmenopausal bleeding where as in our study the reported prevalance was only 7(14%) to be atrophy [13,23,14,15] . Meyer et al postulated the reason for the post-menopausal bleed in senile endometrium to be sclerotic degeneration of endometrial vessels whereas Hourihan et al stated that the anatomical vascular variations or local abnormal haemostatic mechanisms in the uterus to be the cause.…”
Section: Resultssupporting
confidence: 50%
“…If we take MBI and JSPE subscales into account, Pakistani physicians had greater mean EE and DP scores on MBI, but a low PT, CC and SIPS mean score on JSPE than French physicians [2]. In the light of a study conducted in Singapore, Pakistani physicians had a lower mean score of empathy [17].…”
Section: Discussionmentioning
confidence: 90%